2016
DOI: 10.1038/srep21554
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification increases copper toxicity differentially in two key marine invertebrates with distinct acid-base responses

Abstract: Ocean acidification (OA) is expected to indirectly impact biota living in contaminated coastal environments by altering the bioavailability and potentially toxicity of many pH-sensitive metals. Here, we show that OA (pH 7.71; pCO2 1480 μatm) significantly increases the toxicity responses to a global coastal contaminant (copper ~0.1 μM) in two keystone benthic species; mussels (Mytilus edulis) and purple sea urchins (Paracentrotus lividus). Mussels showed an extracellular acidosis in response to OA and copper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 59 publications
6
41
0
Order By: Relevance
“…At pH 7.6, regardless of temperature, gonad development was reduced and in some individuals inhibited. The T. gratilla were able to compensate their acid-base balance in moderate acidification but less so in the lowest pH treatment, as reported for other sea urchin species [22,25,27,49]. Increased temperature caused acidification of the coelomic fluid, probably due to increased respiratory acidosis of the coelom.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…At pH 7.6, regardless of temperature, gonad development was reduced and in some individuals inhibited. The T. gratilla were able to compensate their acid-base balance in moderate acidification but less so in the lowest pH treatment, as reported for other sea urchin species [22,25,27,49]. Increased temperature caused acidification of the coelomic fluid, probably due to increased respiratory acidosis of the coelom.…”
Section: Discussionsupporting
confidence: 59%
“…Maintenance of organism acid -base balance is crucial for physiological function and is a significant energetic cost that affects energy partitioning between fitness traits such as growth and reproduction [25]. Several studies have shown that sea urchins can maintain their acid-base balance at near-future levels of acidification, but this is likely to be energetically costly [26,27], especially in combination with warming [28].…”
Section: Introductionmentioning
confidence: 99%
“…Experts have predicted a drop in seawater pH by 0.3 to 0.4 units by the end of the century and concluded that average oceanic pH will decrease altogether by 0.8 units by 2300 (Caldeira and Wickett, 2003;Feely et al, 2009;IPCC, 2013). If such acidification trend continues to intensify, a wide range of marine invertebrate species (Fabry et al, 2008;Kroeker et al, 2013;Orr et al, 2005), including 63% of echinoderms and 51.6% of mollusks, will have difficulty maintaining healthy and normal physiological activities (Lewis et al, 2016). For example, the exposure to acidified seawater strongly affects immune parameters in Chamelea gallina and Mytilus galloprovincialis (Matozzo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that CO 2 -induced pH reduction impacts bivalve physiology by changing extracellular acid–base balance2627, metabolic activities28 and feeding2930. A rise in pCO 2 levels can induce changes in the extracellular acid–base balance that can produce metabolic disturbances, adversely affecting relevant biological processes, such as calcification, metabolism, growth and fitness3132.…”
mentioning
confidence: 99%